The impact of fixation methods on the risk of revision in ACL reconstruction - a study from the Scandinavian ACL registries, 2004-2011. Issue 3 (23rd March 2016) - Persson, Andreas; Gifstad, Tone; Forssblad, Magnus; Lind, Martin; Engebretsen, Lars
Aims and Objectives: The hamstring autograft is one of the most common grafts used for anterior cruciate ligament reconstruction (ACLR) and a large number of fixation methods are available. There are no studies investigating the risk of revision for specific fixation devices. Revision ACLR is a relatively rare event and large registry-based prospective studies make it possible to analyze differences in risk of revision according to clinical and demographic factors. The aim of the present registry-based study was to describe the current use of fixation method and to compare risk of revision between various femoral and tibial fixation methods in Scandinavia during the study period. Materials and Methods: A total of 38 666 patients undergoing primary ACL reconstructions in the period 2004-2011 were included in the present study. Less frequently used fixation devices were grouped according to the point of graft fixation. To compare the risk of revision between various fixation methods, the multiple Cox proportional hazard (PH) regression model was applied. Hazard rate ratios (HR with 95% confidence interval (CI)) were reported as measure of effect. Results: The median follow-up time was 3 years (range 0 to 8 years). The present data included a total of 1042 revision ACL reconstructions. Based on a Cox PH regression model stratified for country and mutual adjustment for gender, age at surgery (five-year categories), activity at the time when the primary injury occurred, femoral fixation and tibial fixation, we found a significantly lower risk of revision for the transfemoral fixation devices Rigidfix (0.7 (0.6-0.8)) and Transfix (0.7 (0.6-0.9)) compared with the cortical device Endobutton (ref.). The same model showed that a retro interference screw used for tibial fixation had a higher risk of revision (1.9 (1.3-2.9)) compared with a standard interference screw (ref.). Conclusion: In view of the findings in the present study, both femoral and tibial fixation method of hamstring autografts seem to be of significance when evaluating the risk of revision.